Caries Incidence Is Associated with Wasting among Cambodian Children. (February 2023) - Turton, B.; Sullivan, S.; Chher, T.; Hak, S.; Sokal-Gutierrez, K.; Wieringa, F.; Singh, A.
Evidence suggests that dental caries is associated with chronic and acute malnutrition, manifested as stunting and wasting in children. However, studies have not always appropriately accounted for confounding factors or for the temporal ordering between exposure and outcome. This study examined relationships between the development of caries lesions with subsequent stunting and wasting outcomes using data from a population-based cohort in Cambodia. Caries incidence was assessed based on the presence of a new cavitated carious lesion or a new pulpally involved lesion across a 6-mo observation period. Anthropometric measurements were taken at regular intervals. Effects of carious lesions on stunting and wasting were assessed using inverse probability treatment weighting, adjusting for potential confounders, using z scores for height-for-age (HAZ) and weight-for-height (WHZ) as outcomes. In total, 894 children (mean age 20 mo at baseline) were followed over 2 y. At baseline, 350 (39.1%) were identified as having stunting malnutrition. At follow-up, 58 (6.5%) had a new pulpally involved lesion. There was no association between incidence of cavitated or pulpally involved carious lesions at follow-up and stunting (relative risk [RR] = 1.06; 95% confidence interval [CI]: 0.75, 1.50). The incidence of pulpally involved carious lesions had an effect on wasting prevalence (WHZ <−2; RR = 1.35; 95% CI: 0.70, 2.62) and WHZ scores (average treatment effect = −0.294; 95% CI: −0.538, −0.050). This study offers evidence that the development of pulpally involved carious lesions has an effect on WHZ scores. Oral health promotion and clinical prevention and management of dental caries should be explored as interventions to promote normal growth and development among preschool children, particularly in low-income settings.